Consolidating poverty alleviation and rural revitalization from the perspective of industrial assistance: China - Sun, Jie; Zhang, Caijing; Wang, Bo (Frontiers in Sustainable Food Systems, 2025)
With the successful completion of the battle against poverty, the Chinese government now faces the critical challenge of further consolidating the outcomes of poverty alleviation while simultaneously advancing comprehensive rural revitalization. Ensuring an effective connection between poverty alleviation efforts and the rural revitalization strategy has become a key priority. Poverty alleviation focused on eliminating absolute poverty by providing targeted assistance, whereas rural revitalization seeks to promote comprehensive development through inclusive and sustained support. In contrast to the former’s focus on specific households, rural revitalization not only considers welfare benefits but also emphasizes the importance of efficiency. In this context, industrial assistance emerges as a critical factor in bridging the gap between poverty alleviation and rural revitalization, as it significantly impacts both income growth and distribution. Thus, an important issue for policymakers is how to design effective industrial support policies that balance the need for raising income levels with the goal of reducing income disparities, addressing both efficiency and welfare concerns. Accordingly, this paper focuses on the scope of industrial assistance and examines the differential impacts of various industrial assistance targets on household income and income inequality among farmers, using panel survey data from Yunnan Province for empirical analysis. The research found that as the proportion of low human capital groups in industrial assistance targets decreases, farmers’ income increases and income inequality among farmers increases, as opposed to providing industrial assistance only to low human capital groups. This may be because reducing assistance to groups with low human capital, while improving overall income growth, has led to a widening income gap between different groups, as more resources tend to be directed toward those with higher levels of human capital. For this research area, the empirical results show that if only households listed in the poverty registration system are considered as low human capital groups, it is more reasonable for low human capital groups to account for 50% of industrial assistance targets, at which ratio both welfare and efficiency objectives can be achieved. If marginal households are also considered as low human capital groups, this ratio can be further increased.